Assessing the Level of Evidence for Interventions Used for Repeat Pregnancy in Teens for Possible Integration Into Evidence-Based Practice: A Review of Literature for Studies Carried out in the USFrom 1990 - 2021 (International Journal of Studies in Nursing, 2022)
Background: Repeat teen pregnancy among adolescents represents an important public health challenge worldwide as well as in the USA. Repeat teen pregnancy negatively impacts teen mother and the child, in enormous ways. It can cause emotional, psychological and educational challenges, as well as affect the life and opportunities of young mothers and their children. The children of teenage mothers are more likely to have lower school achievement and to drop out of high school, have more health problems, be incarcerated at some time during adolescence, give birth as a teenager, and face unemployment as a young adult. Understanding the levels of evidence of the interventions for adolescent repeat pregnancy can provide guidance to health practitioners and decision makers in selecting an intervention. The aim of this review is to assess the level of evidence of repeat pregnancy interventions conducted in the U.S. (United States) for possible integration into evidence-based practice. Methods: We focused on articles conducted in the U.S. and published between 1990 and 2021. We searched for articles in: The Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, EMBASE, Social Science Citation Index, Science Citation Index, Dissertations, Abstracts Online, PsycINFO, CINAHL, POPLINE, and the reference lists of articles. Research Question: „What are the levels of evidence for interventions for teen repeat pregnancy?‟ Selection criteria: We included and evaluated any intervention that aimed to promote spacing of 2nd birth and reduced repeat teen pregnancies in adolescents ages 13 –19 years. Results: We retrieved fifty-two (52) primary repeat pregnancy intervention studies conducted in the U.S. from 1990 to 2021. Twenty-five (25) interventions met the inclusion criteria and were statistically significant. There were 12 randomized control studies that were statistically significant and met Level I evidence. Six (6) Quasi-experimental studies that were statistically significant and met Level II evidence. There were five (5) Cohort studies that were statistically significant, one prospective and four retrospective studies and met Level III evidence. Two descriptive studies of Level IV evidence. Conclusion: Interventions, can be categorized into: home visitation, peer support, school based and comprehensive interventions including contraceptive use. There were also disparities in the intervention follow-ups, components, study location, statistical analyses and persons conducting the intervention. These disparities, made it difficult to compare and contrast the different interventions. We were able to successfully assign Levels of evidence to each intervention. We identified Twelve (12) Level I; Six(6) Level II; five (5) Level III and two (2) Level IV.